Participation in Leisure Activities by Portuguese Children With Cerebral Palsy. Issue 6 (December 2020) - Vila-Nova, Fabio; Oliveira, Raul; Cordovil, Rita
Leisure participation contributes to the health and wellbeing of children with and without physical disabilities. In the present cross-sectional study, we aimed to assess the influence of child and family factors on leisure activity participation of children with cerebral palsy (CP) aged 8-18 years. A convenience sample of 69 participants with CP (M age = 12.75 years, SD = 2.95; 45 males) responded to the Children's Assessment of Participation and Enjoyment questionnaire to report participation diversity, frequency, companies, environment and enjoyment in leisure activities. From these questionnaires, we used descriptive statistics to summarize overall participation, two activity domains (formal and informal) and five activity types (recreational, social, active physical, skill-based, and self-improvement). Regression analysis assessed child and family factors' influence on participation. On average, children with CP were involved in 21 leisure activities in the last four months. Within activity types, social and recreational activities were the most frequently reported. Participation in physical and skill-based activities was low. Overall children with CP experienced high enjoyment with engagement in leisure activities. Collectively, factors of age, cognitive function, gross motor function, and mother's education level predicted 33% of activity diversity and 30% of activity frequency. We concluded that children with CP show diverse leisure activity participation and high leisure activity enjoyment. Health, education and sports professionals should consider the child's functional profile and family context when promoting participation.